Relationship Of Mom's Knowledge On The Hazards Of Ready Food (Junk Food) To Children Who Experience Overweight At Negeri SD 054903 UPL Kec. Wampu Kab. Langkat - Yusra; Ardianto; Srinur Nilawati; Bagusda Kelana Putra; Indah Rahmaini Hayat; Dewi Andini; Ferry Tri Wahydi (Institute of Computer Science (IOCS), 2020)
Researchers have conducted an initial survey of mothers whose children attend schoolat SD Negeri 054903 UPL Kec. Wampu Kab.Langkat with8 mothers who were elementary school children, 4 of whom said their children often consumed fast food (junk food) and from the observations, 4 of these children experienced overweight or weight gain.The purpose of the study was to determine the relationship between mother's knowledge of the dangers of fast food (junk food) For Children Who Are Overweight at SD Negeri 054903 UPL Kec. Wampu Kab. Langkat Year 2020. The research method used is to use a cross-sectional analytical study design to determine the relationship between mother's knowledge of the dangers of fast food (junk food) In Children Who Are Overweight. The population taken in this study were mothers who have children who attend SD Negeri 054903 UPL Kec. Wampu Kab.Langkat as many as 120 people. The conclusion that can be drawn from this study is that the majority of mothers' knowledge is good as many as 23 respondents (76.7%) and the minority of mothers' knowledge is sufficient as many as 4 respondents (13.3%) and less by 3 respondents (10.0%). The majority of the majority of fast food is not consumed by 23 respondents (76.7%) and the minority is consumed by 7 respondents (23.3%). There is a Relationship between Mother's Knowledge of the Dangers of Junk Food for Overweight Children at SD Negeri 054903 UPL Kec. Wampu Kab. Langkat Year 2021 obtained p.value = 0.000 at df = 1 where sig < (0.000 < 0.05).